Regulatory relationships among aldB, ampH, and acoR and their impact on β-lactam susceptibility in Phytobacter diazotrophicus - Lin, Jiansheng; Zheng, Jingyang; Wang, Gaoxiong (Frontiers in Microbiology, 2025)
BackgroundPhytobacter diazotrophicus (P. diazotrophicus) is an emerging opportunistic pathogen responsible for various human infections. However, it remains unclear whether aldehyde dehydrogenase B (aldB) mediates antibiotic resistance in P. diazotrophicus, and whether acetoin catabolism operon regulator (acoR) gene is associated with antibiotics. This study aims to explore the association between the aldB gene and bacterial susceptibility to β-lactam antibiotics, investigate the potential mechanism by which aldB mediates antibiotic resistance, and clarify the regulatory mechanism of aldB by the upstream adjacent gene acoR.MethodsGene knockout was performed using homologous recombination. The minimum inhibitory concentrations (MICs) of 12 β-lactam antibiotics were determined using the MH agar plate dilution method. RNA transcriptome analysis was performed on the wild-type and aldB knockout strains of P. diazotrophicus Pd1. mRNA expression levels were measured using real-time quantitative polymerase chain reaction (qPCR). The binding of the purified AcoR-HTH protein to PaldB was analyzed using electrophoretic mobility shift assays (EMSA). Ceftazidime was used for antibiotic stimulation tests.ResultsCompared with the wild-type strain, the aldB knockout strain exhibited significantly increased MICs for carbenicillin, cefalotin, cefoxitin, cefuroxime, cefotaxime, ceftazidime, cefepime, and aztreonam by at least 2-, 2-, 2-, 4-, 4-, 4-, 2-, and 4-fold, respectively. RNA transcriptome sequencing revealed that ampH was most significantly downregulated in the aldB knockout strain, which was confirmed by qPCR. Compared with the wild-type strain, the ampH-knockout strain exhibited significantly increased MICs for carbenicillin, piperacillin, cefalotin, cefoxitin, cefuroxime, cefotaxime, ceftazidime, cefepime, aztreonam, and ertapenem by at least 2-, 4-, 8-, 4-, 4-, 4-, 4-, 4-, 4-, and 2-fold, respectively. Compared with the wild-type strain, the acoR knockout strain exhibited significantly increased MICs for carbenicillin, piperacillin, cefalotin, cefoxitin, cefuroxime, cefotaxime, ceftazidime, cefepime, aztreonam, and ertapenem by at least 2-, 4-, 4-, 8-, 4-, 8-, 8-, 4-, 4-, and 2-fold, respectively. Compared with the wild-type strain, the acoR knockout strain significantly downregulates the mRNA expression of aldB. The sequence ACGACACAGTTCGCGAA was identified as a recognition site for AcoR in P. diazotrophicus through software alignment and EMSA experiments. Compared with the untreated wild-type strain, aldB mRNA expression levels in the ceftazidime-stimulated wild-type strain reduced significantly.ConclusionIn P. diazotrophicus, aldB and acoR reduced some β-lactam resistance by facilitating ampH and aldB expression, respectively. This is the first report that links acoR to β-lactam antibiotics and demonstrates that AcoR positively regulates aldB. Under ceftazidime stress, P. diazotrophicus reduced aldB expression to increase its tolerance to the antibiotic. The discovery of the mechanism by which AcoR regulates aldB expression provides preliminary evidence for subsequent research on drug resistance mechanisms.